PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Karima Anisa Safitri; Dul Muid (Diponegoro Journal of Accounting, 2020)
This study aims to examine the factors that affect the company’s tax avoidance using effective tax rate as an indicator. There are several factors used in this research consisted of corporate social responsibility disclosure, profitability, leverage, capital intensity and firm size. The purpose of this study is to empirically examine whether the corporate social responsibility disclosure, profitability, leverage, capital intensity and firm size affect the tax avoidance in manufacturing companies listed in Indonesia Stock Exchange. The analysis technique that being used to test the hypotheses is multiple linear regression analysis.The result shows that corporate social responsibility disclosure has positive significant on tax avoidance, profitability has negative significant on tax avoidance. Meanwhile, leverage, capital intensity and firm size has no significant influence on tax avoidance.